Multi-targeted 1H/19F MRI unmasks specific danger patterns for emerging cardiovascular disorders - Flögel, Ulrich; Temme, Sebastian; Jacoby, Christoph; Oerther, Thomas; Keul, Petra; Flocke, Vera; Wang, Xiaowei; Bönner, Florian; Nienhaus, Fabian; Peter, Karlheinz; Schrader, Jürgen; Grandoch, Maria; et al. (Nature communications, 2021)
Prediction of the transition from stable to acute coronary syndromes driven by vascular inflammation, thrombosis with subsequent microembolization, and vessel occlusion leading to irreversible myocardial damage is still an unsolved problem. Here, we introduce a multi-targeted and multi-color nanotracer platform technology that simultaneously visualizes evolving danger patterns in the development of progressive coronary inflammation and atherothrombosis prior to spontaneous myocardial infarction in mice. Individual ligand-equipped perfluorocarbon nanoemulsions are used as targeting agents and are differentiated by their specific spectral signatures via implementation of multi chemical shift selective 19 F MRI. Thereby, we are able to identify areas at high risk of and predictive for consecutive development of myocardial infarction, at a time when no conventional parameter indicates any imminent danger. The principle of this multi-targeted approach can easily be adapted to monitor also a variety of other disease entities and constitutes a technology with disease-predictive potential. The prediction of major cardiovascular events is still an unsolved problem. Here, the authors present a multi-color, multi-targeted non-invasive imaging technology that allows reliable in vivo identification of silent but prognostically highly relevant danger patterns prior to myocardial infarction in mice.